Meal size effects on the postprandial metabolic response of Bothrops alternatus (Serpentes: Viperidae) - Gavira, Rodrigo S. B. [UNESP]; Andrade, Denis V. [UNESP] (FapUNIFESP (SciELO), 2013)
We examined the effects of meal size on the postprandial metabolic response of the lancehead Bothrops alternatus (Duméril, Bibron & Duméril, 1894), fed mice equaling to 5, 10, 20, and 40% of the snake's body mass. The maximum O2 consumption rates measured during digestion increased with meal size, reaching levels up to 2.8-7.8-fold higher than the metabolic rate measured during fasting. Specific Dynamic Action (SDA) duration also increased with meal size, lasting from 54 to 212 hours to complete. Under our experimental conditions, 30°C, the majority of our snakes failed to completely digest prey with a relative size of 40%. The SDA coefficient ranged from 17 to 27% of the energy content of the meal and was not affected by meal size. © 2013 Sociedade Brasileira de Zoologia All rights reserved.
Keywords: Metabolism; Postprandial; Prey size; Snakes